Electrochemical Performance and Degradation Analysis of an SOFC Short Stack Following Operation of More than 100, 000 Hours. Issue 16 (1st January 2019) - Fang, Qingping; Blum, Ludger; Stolten, Detlef
Abstract : From August 2007 to January 2019, a two-layer solid oxide fuel cell (SOFC) short stack of a planer design with zirconia-based, anode-supported cells (ASC) and ITM interconnectors (with 26% chromium content) was tested with hydrogen and compressed air at a furnace temperature of 700°C for more than 100, 000 hours, of which ∼93, 000 were in constant current mode, with a current density of 0.5 Acm −2 and with a fuel utilization of 40%. The calculated voltage degradation rate slowly decreased, from ∼8.0 mV/kh (∼1.0%/kh) for the first 40, 000 h to ∼1.4 mV/kh (∼0.2%/kh) for the subsequent operation under load, indicating different dominating degradation mechanisms. The average voltage and area-specific resistance (ASR) degradation rates for the complete operating period under electrical load were 0.5%/kh and 2.5%/kh, respectively. Electrochemical impedance spectroscopy (EIS) was also implemented at the end of the testing period for the purpose of electrochemical characterization and a degradation analysis. The post-mortem analysis of the stack is currently in preparation. In this study, the performance and degradation behavior of the stack and cells are analyzed and discussed on the basis of the electrochemical measurements collected.